Test-Photostability of pulsed laser deposited amorphous thin films from Ge-As-Te system - Hawlová, P. (Sci Rep, 2015)
Amorphous thin films from Ge-As-Te system were prepared by pulsed laser deposition to study their intrinsic photostability, morphology, chemical composition, structure and optical properties. Photostability of fabricated layers was studied by spectroscopic ellipsometry within as-deposited as well as relaxed (annealed) layers. For irradiation, laser sources operating at three wavelengths in band gap region of the studied materials were employed. The results show that lowest values of photorefraction accompanied with lowest changes of band gap values were exhibited by Ge(20)As(20)Te(60) thin films, which are therefore considered as the layers with highest photostability in relaxed state. The structure of the films is discussed based on Raman scattering spectroscopy data.